Pharmacological actions of the bioactive compounds of Epimedium on the male reproductive system: current status and future perspective - Song-Po Liu; Yun-Fei Li; Dan Zhang; Chun-Yang Li; Xiao-Fang Dai; Dong-Feng Lan; Ji Cai; He Zhou; Tao Song; Yan-Yu Zhao; Zhi-Xu He; Jun Tan; et al. (Asian Journal of Andrology)
Compounds isolated from Epimedium include the total flavonoids of Epimedium, icariin, and its metabolites (icaritin, icariside I, and icariside II), which have similar molecular structures. Modern pharmacological research and clinical practice have proved that Epimedium and its active components have a wide range of pharmacological effects, especially in improving sexual function, hormone regulation, anti-osteoporosis, immune function regulation, anti-oxidation, and anti-tumor activity. To date, we still need a comprehensive source of knowledge about the pharmacological effects of Epimedium and its bioactive compounds on the male reproductive system. However, their actions in other tissues have been reviewed in recent years. This review critically focuses on the Epimedium, its bioactive compounds, and the biochemical and molecular mechanisms that modulate vital pathways associated with the male reproductive system. Such intrinsic knowledge will significantly further studies on the Epimedium and its bioactive compounds that protect the male reproductive system and provide some guidances for clinical treatment of related male reproductive disorders.